Business Planning Study for the Packaged Sambal Brand Neraka Sambal - Putra, Ronald Fajar Ardiva; Handrito, Radityo Putro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to analyze the feasibility and business prospects of establishing Neraka Sambal, a packaged sambal business, by developing a comprehensive business plan to support strategic development and sustainable growth in the competitive food industry. Design/Methodology/Approach – This study employs a descriptive qualitative research approach supported by literature studies. Data were collected through business analysis observations, competitor product trials, interviews, and documentation. The collected data were analyzed to evaluate key business aspects, including product development, marketing strategy, operations, production processes, management, finance, and business development strategies. Findings – The results indicate that Neraka Sambal has strong potential to compete in the packaged sambal market. The proposed business plan emphasizes product consistency, product innovation, effective marketing strategies, operational and production design, managerial planning, financial management, and market expansion strategies. These strategic initiatives provide a foundation for improving competitiveness and achieving sustainable business growth in the food industry. Originality/Value This research is original in developing a comprehensive business plan specifically for a packaged sambal product within a local market context. The findings provide practical value by offering an integrated framework covering production, marketing, finance, and innovation strategies to support sustainable business growth.